A Review of the Molecular Mechanisms Underlying the Development and Progression of Cardiac Remodeling. (2nd July 2017) - Schirone, Leonardo; Forte, Maurizio; Palmerio, Silvia; Yee, Derek; Nocella, Cristina; Angelini, Francesco; Pagano, Francesca; Schiavon, Sonia; Bordin, Antonella; Carrizzo, Albino; Vecchione, Carmine; Valenti, Valentina; et al.
Abstract : Pathological molecular mechanisms involved in myocardial remodeling contribute to alter the existing structure of the heart, leading to cardiac dysfunction. Among the complex signaling network that characterizes myocardial remodeling, the distinct processes are myocyte loss, cardiac hypertrophy, alteration of extracellular matrix homeostasis, fibrosis, defective autophagy, metabolic abnormalities, and mitochondrial dysfunction. Several pathophysiological stimuli, such as pressure and volume overload, trigger the remodeling cascade, a process that initially confers protection to the heart as a compensatory mechanism. Yet chronic inflammation after myocardial infarction also leads to cardiac remodeling that, when prolonged, leads to heart failure progression. Here, we review the molecular pathways involved in cardiac remodeling, with particular emphasis on those associated with myocardial infarction. A better understanding of cell signaling involved in cardiac remodeling may support the development of new therapeutic strategies towards the treatment of heart failure and reduction of cardiac complications. We will also discuss data derived from gene therapy approaches for modulating key mediators of cardiac remodeling.